A moderated mediation model of the relationship between participatory decision-making and team performance in hotel industry - Yunho Ji; Jangheon Han (Global Business & Finance Review (GBFR), 2021)
Purpose: This study aimed to verify the impact of participatory decision-making (PDM) on team performance (TPF) in the hotel's department/team. In particular, it investigated the role of a mediator for creative self-efficacy (CSE) in the relationship between PDM and TPF. This study determined the optimal decision-making process in a service organization by verifying the controlled mediating effect of collective efficacy (CEF) in the relationship among PDM, CSE, and TPF. Design/methodology/approach: In this study, the 242 samples comprised luxury hotel workers. The analysis verified the hypothesis set by means of causal correlations among four variables using regression analysis and the process macro developed by Hayes (2013). Findings: The study revealed significant effects through the medium of CSE, although PDM did not have a direct impact on TPF. The moderating mediating effect of CEF on the mediating effect of CSE in the relationship between PDM and TPF was statistically significant. Research limitations/implications: This study focused on luxury hotels. The same hierarchy and team culture were assumed without considering the specific characteristics of each hotel team or department. Originality/value: This study proposed a suitable decision-making process model for efficient operation and employee motivation in hotel companies. The findings will contribute to a horizontal and open organizational culture, as well as the spread of PDM.
Keywords: 650; Collective Efficacy; Creative Self-efficacy; Hotel Business; Participatory Decision-making; Team Performance